The London Agreement and the cost of patenting in Europe - Bruno Van Pottelsberghe de la Potterie; Malwina Mejer (Bruegel, 2008)
This paper analyses the consequences for the European Patent System (EPS) of the recently ratified London Agreement (LA), which aims to reduce the translation requirements for patent validation procedures in 15 out of 34 national patent offices. The simulations suggest that the cost of patenting has been reduced by 20 to 30 percent since the enforcement of the LA. With an average translation cost saving of exteuro3,600 per patent, the total savings for the business sector amount to about exteuro220 millions. The fee elasticity of patents being about -0.4, one may expect an increase in patent filings of eight to 12 percent. Despite the translation cost savings, the relative cost of a European patent validated in six (thirteen) countries is still at least five (seven) times higher than in the United States.
Keywords: P14; P51; O34; 330; European patent system; London Agreement; patent fees; translation costs; fee elasticity; Internationales Patentrecht; Gebühr; Übersetzung; Kosten; EU-Staaten